Novel Naturally Occurring Mutations of Enterovirus 71 Associated With Disease Severity - Chang, Chih-Shin; Liao, Chun-Che; Liou, An-Ting; Chou, Yi-Chun; Yu, Ya-Yen; Lin, Chi-Yung; Lin, Jen-Shiou; Suen, Ching-Shu; Hwang, Ming-Jing; Shih, Chiaho (Frontiers in Microbiology, 2021)
Infection with the re-emerging enterovirus 71 (EV-A71) is associated with a wide range of disease severity, including herpangina, encephalitis, and cardiopulmonary failure. At present, there is no FDA-approved therapeutics for EV-A71. Early diagnosis for the high-risk children is the key to successful patient care. We examined viral genome sequences at the 5’ untranslated region (UTR) and the capsid protein VP1 from 36 mild and 27 severe cases. We identified five EV-A71 mutations associated with severe diseases, including 1) the 5’ UTR mutations C580U, A707G, C709U; 2) a VP1 alanine-to-threonine mutation at position 280 (280T), and 3) a VP1 glutamic acid-to-(non-glutamic acid) at position145 (145(non-E)). SCARB2 is a known entry receptor for EV-A71. Based on a recent cryoEM structure of the EV-A71-SCARB2 binding complex, VP1-280T is near the binding interface between the VP1-VP2 complex and its entry receptor SCARB2. A de novo created hydrogen bonding between the mutant VP1-280T and the VP2-139T, could help strengthen a web-like interaction structure of the VP1-VP2 complex. A stabilized loop turn of VP2, once in contact with SCARB2, can enhance interaction with the host SCARB2 receptor for viral entry. Our findings here could facilitate early detection of severe cases infected with EV-A71 in clinical medicine. In addition, it opens up the opportunity of functional studies via infectious cDNA cloning, site-directed mutagenesis, and animal models in the future.